Gender Disparities in Medical and Dental Admissions: Students' Perspectives on Barriers - Nabiha Farasat Khan; Muhammad Ilyas; Usama Saeed Usama; Muhammad Saeed; Muhammad Saim; Raz Muhammad (Journal of University College of Medicine and Dentistry)
Objectives: To explore the gender distribution trends in the MDCAT test, MBBS, and BDS admissions at Bolan Medical College (BMC), Quetta, from 2019 to 2024, and to gather students' perceptions regarding the barriers faced by female students in medical education.